Peningkatan Produktivitas Peternak Unggas Melalui Penerapan Alat Penetas Telur Otomatis di Kelurahan Jabungan - Kholis, Nur; Respati, Sri Mulyo Bondan; Hasan, Muhammad Nur; Albab, Muhammad Ulil (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
Jabungan Village is one of the areas with great potential in the poultry farming sector in Semarang City. Most farmers still use traditional methods in the egg hatching process, which depends on the mother hen. This method has limitations in terms of capacity, success rate, and time efficiency. This community service activity aims to increase poultry farmers' productivity through the application of automatic egg incubators based on temperature and humidity control systems. The implementation methods include a partner needs survey, tool design, training in use, and operational assistance. The results of the activity show a 26% increase in hatchability, a reduction in hatching time from 21 to 20 days, and an increase in farmers' knowledge of modern hatching management. This program has had a positive impact on the efficiency and sustainability of small farmers' businesses in Jabungan.